Bio-inspired synthesis of silver nanoparticles from leaf extracts of Cleistanthus collinus (Roxb.): its potential antibacterial and anticancer activities - Mohanta, Yugal Kishore; Panda, Sujogya Kumar; Syed, Asad; Ameen, Fuad; Bastia, Akshaya Kumar; Mohanta, Tapan Kumar (IET nanobiotechnology, 2018)
In this investigation, the biological synthesis method was adopted to synthesise silver nanoparticles (AgNPs) by using the leaf extracts of Cleistanthus collinus (C. collinus). This plant has traditionally been used to remove the harmful pest from the agriculture field. Leaf extract of C. collinus was used as bioreductant on the precursor solvent of AgNO3. The synthesised AgNPs were characterised by spectroscopic method such as UV–vis spectroscopy, attenuated total reflection Fourier transform infrared spectroscopy, dynamic light scattering and microscopic method by field-emission scanning electron microscopy analysis. The AgNPs were studied for both antibacterial and antifungal activities and found to exhibit potential antibacterial activity against Bacillus subtilis, Staphylococcus aureus and Pseudomonas aeruginosa. The anticancer activity of AgNPs was screened against A-431 osteosarcoma cell line by [3-(4, 5-dimetheylthiazol-2)-2, 5 diphenyl tetrazolium bromide] assay and the IC50 value was found to be 91.05 ± 1.53 μg/ml. This trend of eco-friendly stable synthesis of AgNPs could prove a better substitute for the chemical methods and offer greater opportunity to use these nanosilvers in agricultural and biomedical sectors.